Exercise and Training to Optimize Functional Motor Performance in Stroke: Driving Neural Reorganization? - Roberta B. Shepherd (Neural Plasticity)
Neurorehabilitation is increasingly taking account of scientific findings. Research areas directing stroke rehabilitation are neurophysiology; adaptability to use and activity; biomechanics; skill learning; and exercise science (task, context specificity). Understanding impairments and adaptations enables a reappraisal of interventions—for example,changes in motor control resulting from impairments (decreased descending inputs, reduced motor unit synchronization), secondary soft tissue changes (muscle length and stiffness changes) are adaptations to lesion and disuse. Changes in interventions include increasing emphasis on active exercise and task-specific training, active and passive methods of preserving muscle extensibility. Training has the potential to drive brain reorganization and to optimize functional performance. Research drives the development of training programs, and therapists are relying less on one-to-one, hands-on service delivery, making use of circuit training and group exercise and of technological advances (interactive computerized systems, treadmills) which increase time spent in active practice, Emphasis is on skill training, stressing cognitive engagement and practice, aiming to increase strength, control, skill, endurance, fitness, and social readjustment. Rehabilitation services remain slow to make the changes necessary to upgrade environments, attitudes, and rehabilitation methodologies to those shown to be more scientifically rational and for which there is evidence of effectiveness.